Outcome in the small for gestational age neonates in their early neonatal period in relation with the cord blood nucleated RBC’s - Reddy, T. Prashanth; Chittam, Ramesh; Kumar T., Sravan; K., Sindhura; Chetty, Sanjeev (International Journal of Contemporary Pediatrics, 2017)
Background: NRBCs are physiologically found only in the peripheral blood of the fetus and neonates. Under all other conditions, NRBC is an indicator of pathology, either increase in erythroid activity or damage to the bone marrow has been suggested that the presence of elevated NRBC in the umbilical cord blood is a sign of fetal hypoxia.1-12. Elevated NRBC is a sign of fetal hypoxia in newborns of mothers with preeclampsia even with well controlled hypertension. Methods: The study period is 1 year from November 2015 to October 2016 on Term SGA babies delivered in Navodaya Medical College Hospital and Research Centre. Inclusion criteria all term SGA and healthy term AGA Newborns. Exclusion criteria were mothers with the following condition: maternal diabetes mellitus, hypertension, preeclampsia, chorioamnionitis and babies with the following conditions meconium stained amniotic fluid, congenital anomalies, twin-to-twin transfusion, severe anemia, cyanotic heart disease. Results: The mean gestational age among control and study group was 18.96 and 19.08 respectively. Low APGAR score (≤5) was seen in 3 cases in the study group. No newborn in control group had low APGAR. Out of 50 babies included in this study,24 babies were delivered by LSCS and 26 babies by normal vaginal delivery. the NRBC count was found to be significantly higher in the SGA babies group as compared to the AGA group and this was statistically significant [p,0.005]. Conclusions: My study showed that NRBC count was higher in SGA babies than term AGA babies but there was no correlation of NRBC count with the outcome in SGA babies.